Особенности экологии чеканов в условиях осушенных площадей Среднего Приднепровья - Кузьменко, В.Я. (Вестник зоологии, 1977)
Saxicola rubetra L. and Saxicola torquat2 L. make their nests on drained areas from the second stage of drainage. Perennial grasses and hay-mowings are the most suitable biotopes. Carabidae, Curculionidae, Hemiptera, etc. are predominant in whinchat and stonechat ration.